FAKTOR RISIKO KEJADIAN ISPA DI DESA SUGIHWARAS KECAMATAN MAOSPATI KABUPATEN MAGETAN JAWA TIMUR TAHUN 2016 - Feny Hardianingtias; Mujiyono .; Hery Koesmantoro (GEMA LINGKUNGAN KESEHATAN, 2016)
Almost 90% of people in Sugihwaras Maospati District have a business of making brick. The burning process was done in their own yard and lead to air population. The purpose of this research is to identify indoor and outdoor physical factor of  Acute Respiratory Infections in that village. Measurement of the physical condition of the houses such as ligthing, temperature, and humidity were done. This research is a descriptive study. The data collection is done by observation, interview, and measurement of the physical condition of the house. The samples of this research are 94 houses taken by proportional random sampling. Then, data were analyzed using distribution tables. The research concluded that Acute Respiratory Infections were influenced by some indoor’s factors, ligthing was 58,51% and by outdoor’s factor was 73,4%, there was still smoke that could be harmful for the people. So the sugestion for villagers who have a business of making brick have to wear mask in the manufacturing process, especially during the burning process.  Keywords : ISPA, Physical Condition of the House